Information system structure and the demand for monitoring costs - Mustapha, Mazlina; Ismail, Hashanah (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
It is claimed that information system structure can affect the coordination, monitoring and controlling of organisational activities, and in turn reduce the costs involved. This paper aims to investigate how the information system structure of an organisation affects its demand and preference for monitoring costs in Malaysian business environment. About 867 questionnaires were distributed to public listed companies in Malaysia, however, only 235 questionnaires were completed and usable for the purpose of the study. Descriptive statistics and regression analysis were carried out to analyze the data. The findings indicate that companies using centralised information system structure have negative and significant relationship with total monitoring costs, this result may be explained by the fact that the agents’ self interest behaviour can be monitored by the centralised system. However the information system structure is not significant when the cost of directorship and auditing are compared. But when internal auditing and external auditing costs are compared, the result indicates that companies with centralised information system structure have significantly more internal auditing costs. This paper contributes to the literature relating to the relationship between information system structures and monitoring costs, especially in Malaysian business settings.